A Operação Lava-Jato nas páginas de opinião da Folha de São Paulo - Geraldini, Bernardo Fogli Serpa (2018)
The mass media are a central element of the contemporary political life, and newspapers, in Brazil, are important mainly because of their ability to set the agenda of other media. In this sense, Folha de S. Paulo has a leading role not only because of its leadership in printed circulation, but also because of its growing virtual audience. Since 2014, its agenda has come to include the coverage of “Operação Lava-Jato” (literally, Operation Car Wash), an investigation carried out by the Brazilian Federal Police in order to inquire into corruption schemes. The object of this research is the editorial section of the Folha de S. Paulo, and the objective is to understand how the operation was portrayed by the newspaper. Thus, due to the importance of this investigation in the Brazilian political scenario, we sought to understand how the Folha de S. Paulo characterized both the operation and the political actors involved in it. To this end, the newspapers’ editorials published throughout almost four years were analyzed. The main method used was framework analysis. In terms of frequency of mentions, the results show that the newspaper initially highlighted individuals associated with the Brazilian Workers’ Party that were involved in the scandals, a highlight that was lessened after the impeachment that took place in 2016. In terms of the frameworks, it was found that at first the operation was praised, after which it was seen as a force disturbant to the political system and from which arose abuse of authority. It was found that the “antipetismo” (bias against the Workers’ Party), already pointed out by other researches, was present under different configurations in the editorials. In addition, it was noted that the Folha de S. Paulo did not embrace the opportunity to hold a debate on the institutional conditions that favor transgressions of the kind investigated by the operation in question.